Water distribution network and Wastewater collection system for Zawata village - Mustafa Amr (My University, 2019)
A water supply system or water supply network is a system of engineered hydrologic and hydraulic components which provide water supply. Our project will be carried out in zawata. The water network in zawata does'nt work efficiently or effectively and It doesn't sufficient for the needs of the population, so it will be evaluated and redesigned to minimize the loss of water and increase its efficiency as much as possible. On the other side, zawata has no sewer network ; so we have to design a sewer network . We have two main object in Our project. The evaluated and redesigned of water network and design sewer networks. .Many parts have to be considered in the project. First of all , the number of population in future depending on increasing rate, the economical evaluation of the project , also we will check the adequacy of the water network to meet the demand in its peak condition . Another important part is to make sure that velocities and pressure values are within the acceptable and designed range. For the sewer network, we have to design the network depending on the consumption of the area from all houses and buildings, and to keep pollution sources away from residential areas. Its clear that the main objectives of the project are to cover the needed demand of water for each house or facility, with minimum cost and with high water quality, and to get rid of the sewage. Methodology starts by collecting data and information from the area of study and from previous studies related to the project, including the demand which is computed from the number of people. And by using the suitable computer programs (WaterCad and SewerCad) this data will be used to design networks which meet the required objectives.